A Study Wordwall Media for Students’ Descriptive Text Writing Skill - Safarina; Wijaya, Mohammad Kurdi (Global Action and Education for Society, 2025)
Writing is one of the important skills in English. However, students often feel bored and struggle with writing learning both in generating ideas and in structuring. Particularly in descriptive text lessons, students often perceive that writing descriptive texts is very difficult. As a teacher, one should provide enjoyable learning experiences by utilizing appropriate learning media. This can help motivate students to engage more actively in their studies, one of which is through the use of Wordwall media. This research aims to determine students' responses to game-based learning media, specifically Wordwall, to assess the descriptive writing abilities. In this study, the researcher employed a descriptive qualitative method, focusing on events occurring in the field. The research was conducted at SMP Al-Ilyasy, with the subjects being XI B students. The data collection techniques used by the researcher included observation, interviews, questionnaires, and documentation. The results of this study have shown that the use of Wordwall media has a significant positive impact on students, particularly in enhancing their skills in writing descriptive texts. The responses provided by the students clearly indicate that Wordwall media not only makes the learning process more effective but also successfully increases their motivation to learn.